Effects of Glycyrrhizin Treatment on Diabetic Cornea - Somayajulu, Mallika (J Ocul Pharmacol Ther, 2021)
Purpose: To test how glycyrrhizin (GLY) affects mouse corneal epithelial cells (MCEC) and the diabetic murine cornea. Methods: Viability of MCEC grown under normal or high glucose (HG) with/without GLY was tested by an MTT assay. In addition, C57BL/6 mice were injected with streptozotocin and a subset of control and diabetic mice received GLY in their drinking water. mRNA and protein levels of proinflammatory and oxidative stress molecules were tested by reverse transcription–polymerase chain reaction (RT-PCR) in both models. Ex vivo studies using human diabetic versus control corneas analyzed proinflammatory and oxidative stress markers using RT-PCR and enzyme-linked immunosorbent assay. Results: GLY protected against loss of cell viability induced by HG and significantly reduced HMGB1, IL-1β, TLR2, TLR4, NLRP3, COX2, SOD2, HO-1, GPX2, and GR1. In vivo, corneas of GLY-treated diabetic mice showed significantly decreased mRNA expression for CXCL2, iNOS, and all molecules listed above; GLY also lowered HMGB1 and IL-1β proteins (in vitro and in vivo). Ex vivo studies using diabetic human corneas revealed elevated mRNA levels of inflammatory and oxidative stress molecules (as listed above for in vivo) versus normal age-matched controls. Protein levels for HMGB1 and IL-1β also were elevated in diabetic human versus control corneas. Conclusions: The data provide evidence that GLY treatment attenuates inflammation and oxidative stress in vitro in MCEC and in vivo in the cornea of diabetic mice. Ex vivo data support the similarities of proinflammatory and oxidative stress data in mouse compared to human, suggesting that GLY treatment would have relevancy to patient care.